PENGEMBANGAN BAHAN AJAR UNTUK MENUMBUHKAN NILAI KARAKTER PEDULI LINGKUNGAN PADA SISWA KELAS IV SEKOLAH DASAR - Saputra, Henry Januar; Faizah, Nur Isti (Profesi Pendidikan Dasar, 2017)
This study was conducted using ADDIE method development procedures with steps include Analysis, Design, Development, Implementation and Evaluation. The research was conducted in SDN Sendangmulyo 03 Semarang. The research subjects in this study were 34 fourth grade students. The data collected in this study is data and data media expert subject matter experts and product testing results data. The average results of students' prior to using EE teaching materials amounting to 64.12 while the average student learning outcomes after the use of teaching materials PLH of 90.51. Then, from the observation of environmental care character on the student obtained the result "Very Good" with an average score of 19. It shows a decent EE instructional materials used as teaching material because it can improve the character of environmental awareness in students. It can be concluded that PLH instructional materials used for teaching in primary schools, especially the fourth grade. His suggestion that EE teaching materials for fourth grade students that have been developed to be implemented in a learning activity to determine the extent of the advantages and disadvantages of these learning products.